Diplomacy and Foreign Policy of Nepal: Perception of the Members of the House of Representatives of Nepal - Kanwar, Kalidas (DAV Research Journal, 2026)
The purpose of this paper is to explore and analyze the perception of the House of Representatives of Government of Nepal (GoN) 2023 to 2025 AD on the diplomacy and foreign policy of Nepal. Further, the research issue concerns the question of what is the understanding of diplomacy and foreign policy of Nepal by the respondents in a discipline for the smooth growth and development of Nepal’s international relations in international political practice. The research is based on quantitative research method that reflects the understanding and perception of the House of Representatives regarding political awareness in respect to diplomacy and foreign policy and its implementation in international political understandings. In this regard, primary data has been collected, analyzed and interpreted using SPSS. The analysis is made on Nepal’s diplomatic relations on two variables – diplomacy and foreign policies within the geo-political and international political environment, particularly in relation to its foreign policy development and execution. Understanding of these variables are fundamental for acquisitive how Nepal navigates its relationships and influences in a complex global environment. The research is based on the soft and smart power strategy based on liberal and constructive theory of International Relations (IR) and foreign policy mechanism.